QUANTIFICATION OF CARBON DERIVED FROM LIGNITE IN SOILS USING MID-INFRARED SPECTROSCOPY AND PARTIAL LEAST SQUARES - Rumpel C.; Janik L.J.; Skjemstad J.O.; Kogel-Knabner I. (My University, 2001)
The total organic carbon (TOC) of many recultivated mine soils is composed of a fraction that is lignite-derived as well as a fraction that is derived from recent plant litter. In these soils, precise quantification of the lignite contribution to the TOC content can only be achieved with expensive and time consuming methods. In the present study, we tested diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy in combination with multivariate data analysis [partial least squares (PLS)] as a rapid and inexpensive means of quantifying the lignite contribution to the TOC content of soil samples. The conceptual approach included analysis of samples with different lignite content (bulk soil and particle size fractions) by DRIFT-spectroscopy and 14C activity measurements. Afterwards, with both data sets a calibration curve was established by PLS and the lignite content predicted from the DRIFT spectra. A good fit was obtained between this approach and the radiocarbon analysis. Loading factors showed that this prediction was based on structural differences between the two organic matter types. We conclude that DRIFT spectroscopy can be used in combination with multivariate data analysis for the differentiation of carbon derived from lignite and carbon derived from recent organic matter in soils.
Keywords: LIGNITE; ORGANIC MATTER; DRIFT SPECTROSCOPY; 14C ACTIVITY; PARTIAL LEAST SQUARES